Principles of issuing fatwa an annotated translation and edition of Sharh 'Uqud Rasm al-Mufti of Muhammad Amin Ibn Abidin al-Shami - Ali, Mohammed Farid (Dar Al Wahi Publication, 2022)
This is a book on Principles of Issuing Fatwa. It is an annotated translation and Edition of Sharh 'Uqud Rasm al-Mufti an epistle written by the 13th century Ottoman Damascus mufti Muhammad Amin more commonly known as Ibn Abidin al-Shami. All his epistles were published in a collection known as Majmu' al-Rasail Ibn Abidin compromising of 31 epistles. Sharh Uqud Rasm al-Mufti is the second epistle in this collection. This book is disclosing methodologies muftis need on day-to-day basis in drafting and issuing fatwas.